Case report: BRAF A598-T599insV mutation as a potential resistance mechanism to alectinib in ALK-rearranged lung adenocarcinoma - Pasau, Thomas; Wauters, Els; Wauters, Isabelle; Duplaquet, Fabrice; Pirard, Lionel; Pop-Stanciu, Claudia; D’Haene, Nicky; Dupont, Michael; Vander Borght, Thierry; Rondelet, Benoît; Ocak, Sebahat (Frontiers in Oncology, 2022)
Anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) have improved the prognosis of advanced-stage non-small cell lung cancer (NSCLC) with ALK rearrangement, but resistance mechanisms limit their efficacy. We describe the case of a 63-year-old man with a stage cIVA ALK-rearranged lung adenocarcinoma who developed a BRAF A598-T599insV mutation as a potential resistance mechanism to alectinib, a second-generation ALK TKI. He was treated with an association of BRAF and MEK inhibitors but death occurred two months after treatment initiation in a context of tumor progression and toxicity. Based on this first report of BRAF A598-T599insV mutation occurring in lung cancer, we discuss resistance mechanisms to ALK TKIs, implications of BRAF mutation in NSCLC, and BRAF A598-T599insV mutation in other cancers.